Maternal education, divorce, and changes in economic resources: Evidence from Germany - Liliya Leopold; Thomas Leopold (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This study investigated the effects of divorce on educational gaps in mothers' economic resources. The results shed new light on two opposing theoretical positions that have informed research on social inequality in the consequences of divorce. Recent extensions of the 'diverging destinies' perspective posit that divorce is more consequential among the disadvantaged than among the privileged. The notion of 'divorce as an equalizer' posits the reverse. Based on data from the German SOEP, we estimated correlated random-effects models to examine educational gaps in divorce-related changes of mothers' household income and risk of poverty. The results are inconsistent with the diverging destinies perspective, as educational gaps in mothers' economic resources did not widen after divorce. Instead, we found partial support for the competing notion of divorce as an equalizer, as higher educated mothers experienced larger declines in household income. Educational gaps in the risk of poverty remained constant.
Keywords: 330